Nebria (Boreonebria) gyllenhali - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Nebria ( Boreonebria ) gyllenhali (Schönherr, 1806) Material. Khabarovsk, 7.06.1970, A. Ryabukhin leg., 1♂; The northern Sikhote-Alin, the Si River at Mukhen, 23.06.1998, E. Novomodnyi leg., 1♀. Distribution. A boreal Holarctic species. In the Palearctic: from Ireland and France in the west to Chukotka, the Commander and the Kuril Islands in the east, from the tundra zone in the north to Southern Europe, the Southern Urals, Mongolia, North Korea, and Hokkaido Island in the south. Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 572, DOI:10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734